Hydrogel systems for targeted cancer therapy - Li, Xinlin; Xu, Xinyi; Xu, Mengfei; Geng, Zhaoli; Ji, Ping; Liu, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
When hydrogel materials with excellent biocompatibility and biodegradability are used as excellent new drug carriers in the treatment of cancer, they confer the following three advantages. First, hydrogel materials can be used as a precise and controlled drug release systems, which can continuously and sequentially release chemotherapeutic drugs, radionuclides, immunosuppressants, hyperthermia agents, phototherapy agents and other substances and are widely used in the treatment of cancer through radiotherapy, chemotherapy, immunotherapy, hyperthermia, photodynamic therapy and photothermal therapy. Second, hydrogel materials have multiple sizes and multiple delivery routes, which can be targeted to different locations and types of cancer. This greatly improves the targeting of drugs, thereby reducing the dose of drugs and improving treatment effectiveness. Finally, hydrogel can intelligently respond to environmental changes according to internal and external environmental stimuli so that anti-cancer active substances can be remotely controlled and released on demand. Combining the abovementioned advantages, hydrogel materials have transformed into a hit in the field of cancer treatment, bringing hope to further increase the survival rate and quality of life of patients with cancer.